South Africa to Burkina Faso: African agricultural innovation in a changing global environment - Katingi, E.; Seré Rabé, Carlos; Longley, K.; Otieno, Y. (2010)
This was the theme that brought together more than 700 hundred diverse participants for the 5th Agriculture Science Week and Forum for Agricultural Research in Africa (FARA) General Assembly, held 19-24 July 2010 in Ouagadougou, Burkina Faso. The FARA Science Week has become a major event in the African agriculture scene and has successfully expanded its stakeholder base beyond the national agricultural research systems to include NGO, government, farmer organization and some private sector participants, as well as several ministers of agriculture.